THU0328 SAFETY AND EFFICACY OF SUBCUTANEOUS TOCILIZUMAB IN SYSTEMIC SCLEROSIS: RESULTS FROM THE OPEN-LABEL PERIOD OF THE PHASE 3 FOCUSSCED TRIAL. (2nd June 2020) - Khanna, D.; Lin, C. J. F.; Spotswood, H.; Siegel, J.; Furst, D.; Denton, C.
Abstract : Background: The anti–interleukin-6 (IL-6) receptor-α antibody tocilizumab (TCZ) demonstrated skin score improvement and forced vital capacity (FVC) preservation in patients with systemic sclerosis (SSc) in a phase 2 randomized controlled trial. 1, 2 Data from the 48-week, double-blind (DB), placebo (PBO)-controlled period of the focuSSced phase 3 trial were previously presented, 3 and open-label (OL) data up to week 96 are presented herein. Objectives: To assess the long-term safety and efficacy of TCZ in SSc patients. Methods: Adult patients with active SSc (≤60-month duration, modified Rodnan skin score [mRSS] 10-35, and elevated acute-phase reactants) treated with PBO or TCZ in the DB period received OL TCZ 162 mg SC weekly from weeks 48 to 96 in the OL period (PBO→OL TCZ and TCZ→OL TCZ, respectively). Exploratory analysis of data up to week 96 included no formal statistical analyses. Changes in mRSS and percent predicted FVC (ppFVC) were assessed. Results: Overall, 92/105 TCZ (88%) and 89/107 PBO (83%) patients entered the OL TCZ treatment period at week 48, and 85/105 TCZ→OL TCZ (81%) and 82/107 PBO→OL TCZ (77%) patients completed treatment up to week 96. Continued decline in mRSS was observed in the OL period for PBO→OL TCZ and TCZ→OL TCZ patients (Table). Change in ppFVC for patients who switched from PBO to TCZ (PBO→OL TCZ) was comparable between weeks 48 and 96 (OL period) to the change in patients who received TCZ from BL to week 48 in the DB period (Table). Rates (95% CI) of serious adverse events from weeks 48 to 96 were 15.8 (8.6, 26.5) per 100 PY for TCZ→OL TCZ patients, 14.8 (7.9, 25.3) per 100 PY for PBO→OL TCZ patients, and 15.4 (11.0, 20.9) for all TCZ exposure over 96 weeks (n = 193). Rates (95% CI) of serious infections were 2.3 (0.3, 8.1) per 100 PY for TCZ→OL TCZ patients, 3.4 (0.7, 10.0) per 100 PY for PBO→OL TCZ patients, and 3.0 (1.3, 5.9) for all TCZ exposure over 96 weeks. One death occurred during the OL period in each arm. Conclusion: Although OL data have to be interpreted with caution, results from OL TCZ treatment show numeric improvements in mRSS and FVC preservation similar to those of the DB period, with a beneficial effect on trajectory of FVC decline in patients who switched from PBO to TCZ. Long-term safety results were consistent with the known safety profile of TCZ, and no new or unexpected events were observed. References: [1]Khanna D et al. Lancet 2016;387:2630-40. [2]Khanna D et al. Ann Rheum Dis. 2018;77:212-20. [3]Khanna D et al. Arthritis Rheumatol 2018;70(suppl 10):abst 898. Disclosure of Interests: Dinesh Khanna Shareholder of: Eicos, Grant/research support from: NIH NIAID, NIH NIAMS, Consultant of: Acceleron, Actelion, Bayer, BMS, Boehringer-Ingelheim, Corbus, Galapagos, Genentech/Roche, GSK, Mitsubishi Tanabi, Sanofi-Aventis/Genzyme, UCB Pharma, Celia J. F. Lin Employee of: Genentech, Helen Spotswood Shareholder of: Roche Products Ltd, Employee of: Roche Products Ltd, Jeff Siegel Employee of: Genentech, Daniel Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Consultant of: AbbVie, Actelion, Amgen, BMS, Cytori Therapeutics, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Speakers bureau: CMC Connect (McCann Health Company), Christopher Denton Grant/research support from: GlaxoSmithKline, CSL Behring, and Inventiva, Consultant of: Medscape, Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Corbus Pharmaceuticals, Acceleron, Curzion and Bayer